PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP KINERJA GURU - Susilo, Susilo; Sutoyo, Slamet (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
This study aims to describe the effect of academic supervision on the performance of rayon 4 elementary school teachers in Rimau Island sub-district. This study uses a quantitative approach with a survey. The technique of data collection uses a questionnaire with a Likert scale. The sample used is a saturated sampling technique or also called a census, the population is sampled in the study the number of samples that the author took as many as 34, where the total population is equal to the number of samples of all teachers of Rayon 4 Elementary School District of Rimau Island. Processing data using simple linear regression and multiple linear regression to find out the effect together. Data collected using questionnaires made percentage. The data collected is tabulated. The results of the study show that the supervision of the principal has a positive effect on the performance of teachers at the Rayon 4 Elementary School in Pulau Rimau District.